The Father, Intratrinitarian "Cause-Principle". Note on an Aspect of the Trinitarian Theology of Basil of Caesarea and Gregory of Nyssa - Capboscq, Alberto Carlos (Teología, 2016)
The fontal character of the Father within the Trinity is a topic always discussed again in Trinitarian Theology and, in this context, often it appeal’s to the Cappadocian Fathers. This note wants to document the use of the notions of “principle-cause” (ἀρχή - αἰτία) in the theological works of Basil the Great and Gregory of Nyssa.